Effects of Paclobutrazol on Growth and Antioxidant Content of Brassica Rapa Var. Oleifera - Yusop, Z; Y Tsan, F; M Jusoh, J; S Sahmat, S (International Journal of Engineering and Technology, 2019)
The experiment was conducted with the main objective was to study the effects of Paclobutrazol (PBZ) on growth and antioxidant content of Brassica rapa var. oleifera. The PBZ was applied at various concentrations (0, 5, 10, 15 and 20 mg /L) through seed soaking and seedling as soil drenching. The growth performance data collection was conducted on weekly basis starting from week 3 until week 6 of planting while antioxidant content analyses were conducted on day 38. It was found that PBZ affected the growth and antioxidant content of Brassica rapa var. oleifera. The soil drenching techniques was found significantly affect the plant height, number of leaves and internode length. Similarly, both ascorbic acid and phenolic content were significantly affected by the technique. It was found that application of 10mg/L and 5mg/L of PBZ has recorded highest amount of ascorbic acid and phenolic content, respectively. This study has proven that the application of PBZ using soil drenching technique on Brassica rapa var. oleifera has contributed to enhancement of its antioxidant content which is also one of the important component in healthy diet intake.Â Â